2022
DOI: 10.1002/srin.202200316
|View full text |Cite
|
Sign up to set email alerts
|

Properties and Structure Evolution of CaO–Al2O3–La2O3 Slags with Various Alkali Metal Oxide Contents

Abstract: To restrain the serious flux-steel reaction, CaO-Al 2 O 3 -La 2 O 3 -based mold flux is designed for continuous casting of La-bearing FeCrAl alloy. The properties and structure of slags with various alkali metal oxide contents are investigated. Results show that with the increase in Na 2 O or Li 2 O contents from 0 to 10 wt%, the melting temperature of slags decreased, and the fluxing effect of Li 2 O is improved. The addition of Na 2 O within 10 wt% reduces the slag viscosity at the temperature range of 1663-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Wang [ 40 ] found that substituting an equivalent number of CaF 2 with B 2 O 3 significantly enhanced the desulfurization ability of the flux. Fan et al [ 41 ] found that the melting temperature and viscosity of a slag decreased as the Li 2 O content increased from 0 wt% to 10 wt%. This was attributed to a decrease in the Q Al 4 fraction from 25% to 9.7% and an increase in [AlO 6 ] octahedra from 0% to 9.02%.…”
Section: Refining Slag and Desulfurization Theorymentioning
confidence: 99%
“…Wang [ 40 ] found that substituting an equivalent number of CaF 2 with B 2 O 3 significantly enhanced the desulfurization ability of the flux. Fan et al [ 41 ] found that the melting temperature and viscosity of a slag decreased as the Li 2 O content increased from 0 wt% to 10 wt%. This was attributed to a decrease in the Q Al 4 fraction from 25% to 9.7% and an increase in [AlO 6 ] octahedra from 0% to 9.02%.…”
Section: Refining Slag and Desulfurization Theorymentioning
confidence: 99%